Evaluasi Program Pembinaan Tenis Lapangan PELTI Kota Palembang - Hendra Mashuri (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2019)
This study aims to 1) evaluate Palembang PELTI tennis coaching program, 2) evaluate PELTI management, athletes, coaches and assistant coaches, facilities and infrastructure, and government support for Palembang's tennis development program, 3) evaluate the selection of coaches and athletes, fostering athletes, training programs, evaluating the PELTI work program and coordinating the tennis coaching program of the city of Palembang, and 4) evaluating the success of the Palembang tennis development program. This study is a program evaluation study using the CIPP method using a qualitative approach. The population of this study was tennis athletes in Palembang. Data collection techniques are observation, in-depth interviews, documentation, and data triangulation. This study produces 1) good Context, 2) Sufficient Input 3) Sufficient Process 4) Sufficient Product. This study concludes that 1) Development Program that is not clear from PELTI in improving athlete performance, 2) Input of PELTI development program is still lacking in the process of selecting athletes, coaches, assistant coaches and minimal funding from the government, 3) Process training program that is not going well, the health of athletes, coaches and assistant coaches who are not guaranteed by the government and there is no special transportation for athletes, 4) Product Program PELTI Coaching has not been able to show results at the national level with real data and facts in the field.